STRATEGIES FOR OPTIMAL PERFORMANCE UNDER STRESS AND PRESSURE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Basketball is a physically and mentally demanding sport that requires specific strategies to perform optimally under stress and pressure. This article discusses the psychological preparation of athletes, stress management techniques, and strategies for achieving the best results under pressure during the game. Research shows that athletes' stress tolerance and performance can be increased through mental preparation and adapted training methods. It also analyzes the physiological and psychological effects of stress, as well as successful strategies used by various athletes. This study provides scientific and practical recommendations for basketball players to achieve optimal results under stress, based on advanced research in the field of sports psychology.